Наукові основи сталого розвитку - Захарченко, Олег Володимирович (My University, 2014)
The study is based on the analysis of such notion as “sustainable development”. It was found that the countries in terms of optimal development can be divided into two groups: those which are on this path (USA, Japan, and EU) and those in which such processes are just beginning (Asia, Latin America and Africa). The range of issues and factors that affect the sustainable development, especially in developing countries, is given. The principles of sustainable development are defined. It has been established that the main components of sustainable development are economic, social and environmental ones; they should be considered only in their interrelation. The model of the component connection of sustainable development is demonstrated. The main strategic trends that underpin sustainable development planning are listed. У статті на основі проведеного аналізу наведено визначення поняття «сталого розвитку». З ’ясовано, що країни за рівнем оптимального розвитку можна поділити на дві групи: які стали на цей шлях (США, Японія, ЄС) і в яких цей шлях тільки починається (країни Азії, Латинської Америки, Африки). Визначено коло проблем і чинників, які негативно впливають на збалансований розвиток, особливо країн, що розвиваються. Розкрито принципи, на яких ґрунтується концепція сталого розвитку. Встановлено, що серед основних компонент сталого розвитку виділяють економічну, соціальну й екологічну, розгляд яких ґрунтується тільки у взаємозв’язку. Наведено модель взаємоз в ’язку складових сталого розвитку. Перераховано основні стратегічні тенденції, на яких базується планування стійкого розвитку.
Keywords: sustainable development; developing countries; developed countries; розвинені країни; сталий розвиток; країни, що розвиваються